2020
DOI: 10.1016/j.dsx.2020.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Coping with diabetes during the COVID – 19 lockdown in India: Results of an online pilot survey

Abstract: Aim: The management of diabetes has become a challenge due to the COVID 19 lockdown. An onlinebased pilot survey was conducted to study how people with diabetes were coping with their Diabetes during the COVID-19 lockdown. Method: The questions were designed in an online survey, Survey Monkey, to conduct this crosssectional study. The link was generated and sent to 100 registered patients of the MV Hospital for Diabetes Royapuram who had not contacted the hospital after the lockdown announcement. The survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
103
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(120 citation statements)
references
References 7 publications
11
103
2
4
Order By: Relevance
“…The impact was greatest amongst the more vulnerable in society, in particular those from lower socio-economic backgrounds. Our results expand the evidence base on the impacts of COVID-19 on access to healthcare in South Asia, [22][23][24][25] making a strong case for measures to protect routine health services, increase the use of digital platforms and provide medication support. [26] Our baseline and follow-up data also enable an accurate assessment of the impact of the COVID-19 pandemic on health behaviours.…”
Section: Covid-19 Non-communicable Disease and Healthy Behaviours Insupporting
confidence: 70%
“…The impact was greatest amongst the more vulnerable in society, in particular those from lower socio-economic backgrounds. Our results expand the evidence base on the impacts of COVID-19 on access to healthcare in South Asia, [22][23][24][25] making a strong case for measures to protect routine health services, increase the use of digital platforms and provide medication support. [26] Our baseline and follow-up data also enable an accurate assessment of the impact of the COVID-19 pandemic on health behaviours.…”
Section: Covid-19 Non-communicable Disease and Healthy Behaviours Insupporting
confidence: 70%
“…The authors also observed a decline in interest in sports such as fitness classes, running, and gym workout [ 8 ]. Nachimuthu et al published a brief survey conducted among 100 Indian patients with DM which revealed that 80% of respondents monitored their diet regularly and engaged in physical activity at home [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare workers who were quarantined, worked in SARS units, or had family or friends infected with SARS, had considerably more anxiety, depression, frustration, fear, and post-traumatic stress than those who had no such experience (Xiang et al, 2020;Wu et al, 2009). Similarly, many published studies have assessed the psychological impact of COVID-19 and have also found high levels of psychological distress (Lai et al, 2020;Chen et al, 2020;Lu et al, 2020;Du et al, 2020;Tan et al, 2020;Consolo et al, 2020;Guiroy et al, 2020;Lei et al, 2020;Ahmed et al, 2020;Ni et al, 2020;Gao et al, 2020;Mazza et al, 2020;Moghanibashi-Mansourieh, 2020;Özdin andÖzdin, 2020, Ozamiz-Etxebarria et al, 2020;González-Sanguino et al, 2020;Sønderskov et al, 2020;Qian et al, 2020;Guo et al, 2020;Tang et al, 2020;Xie et al, 2020;Nachimuthu et al, 2020;Durankuş and Aksu, 2020;Saccone et al, 2020;Salari et al, 2020;Nguyen et al, 2020;. A recent systematic review and meta-analysis has summarized the prevalence of depression and anxiety among healthcare workers during the COVID-19 (Pappa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Italy, Spain, Iran, Israel) have been published (Consolo et al, 2020;Guiroy et al, 2020;Mazza et al, 2020;Moghanibashi-Mansourieh, 2020;Özdin andÖzdin, 2020, Ozamiz-Etxebarria et al, 2020;González-Sanguino et al, 2020;Sønderskov et al, 2020;Nachimuthu et al, 2020;Durankuş and Aksu, 2020;Saccone et al, 2020;Salari et al, 2020;Nguyen et al, 2020;Amin, 2020;Shacham et al, 2020;Jahanshahi et al, 2020;Moccia et al, 2020;Voitsidis et al, 2020;Suzuki, 2020), and some of these studies extended the study population from healthcare workers to the general public (Mazza et al, 2020;Moghanibashi-Mansourieh, 2020;Özdin andÖzdin, 2020, Ozamiz-Etxebarria et al, 2020;González-Sanguino et al, 2020;Sønderskov et al, 2020;Jahanshahi et al, 2020;Moccia et al, 2020;Voitsidis et al, 2020) and patients with pre-existing conditions (e.g. cancer, psychiatry, epilepsy, type 2 diabetes) (Qian et al, 2020;Nachimuthu et al, 2020;Salari et al, 2020; or infected by COVID-19 (Guo et al, 2020Bo et al, 2020). A few studies have suggested that the psychological impact of COVID-19 may be different among healthcare workers, the general public and patients Ni et al, 2020;Salari et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%